1997
DOI: 10.1063/1.118838
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-sensitive, visible-blind GaN photodiodes fabricated by molecular beam epitaxy

Abstract: GaN p–i–n photovoltaic diode arrays were fabricated from epitaxial films deposited on sapphire by molecular beam epitaxy. Peak UV responsivity was 0.11 A/W at 360 nm, corresponding to 48% internal quantum efficiency. Visible rejection over 400–800 nm was 3–4 orders of magnitude. Typical pulsed time response was measured at 8.2 μs. Spectral response modeling was performed to analyze the photocurrent contributions from photogenerated carrier drift in the depletion region and from minority carrier diffusion in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(67 citation statements)
references
References 11 publications
2
64
0
1
Order By: Relevance
“…In calculating the responsivity of the device we take into account contributions to the photocurrent that originate from photogenerated holes in the n-Al 0.1 Ga 0.9 N layer that diffuse towards the depletion region, from the drift of photogenerated carriers in the depletion regions of the Al 0.1 Ga 0.9 N and the GaN, and from the diffusion of electrons in the p-GaN layer diffusing towards the depletion region [4]. The device is assumed to be illuminated through the n-Al 0.1 Ga 0.9 N layer , with reflections at the air/sapphire and the sapphire/detector interfaces taken into account in the model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In calculating the responsivity of the device we take into account contributions to the photocurrent that originate from photogenerated holes in the n-Al 0.1 Ga 0.9 N layer that diffuse towards the depletion region, from the drift of photogenerated carriers in the depletion regions of the Al 0.1 Ga 0.9 N and the GaN, and from the diffusion of electrons in the p-GaN layer diffusing towards the depletion region [4]. The device is assumed to be illuminated through the n-Al 0.1 Ga 0.9 N layer , with reflections at the air/sapphire and the sapphire/detector interfaces taken into account in the model.…”
Section: Resultsmentioning
confidence: 99%
“…Although photoconductive detectors have the desirable property of internal gain, they suffer from well known drawbacks which include high dark currents, DC drift, slow response time, and occasionally spurious photoresponse at long wavelengths. Recently, relatively fast photovoltaic UV detection using GaN p-n diodes or Schottky diodes has been demonstrated [4] [5] [6]. A key advantage of III-nitride detectors over competing devices based on semiconductors with smaller bandgaps (for example UV-enhanced Si photodetectors) is the long wavelength response cut-off which is directly related to the bandgap of the material in the active region and thus does not require external filters.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the growth process have been previously reported [5][6]. The detector epitaxial layers consisted of a 5·10 18 cm -3 n-GaN layer followed by a 5000 Å intrinsic region with unintentional n-type doping in the 10 15 cm -3 decade.…”
Section: Methodsmentioning
confidence: 99%
“…5 It has been recently demonstrated that the large intrinsic piezoelectric coefficients of GaN and AlN are responsible for an anomalously large concentration of two-dimensional electron gas at the AlGaN/GaN interface in GaN/AlGaN heterojunction field effect transistors ͑HFET͒. 6,7 Other possibilities exist for the enhancement of electric properties of contacts to nitrides by piezoelectric engineering as recently demonstrated in the case of Schottky contacts.…”
Section: Introductionmentioning
confidence: 99%